AN IMPROVEMENT CONTROL PERFORMANCE OF AC MOTOR 3 PHASE WATER TOWER CENTRIFUGAL PUMP - Zulkarnain Lubis; Solly Aryza (Jurnal Scientia, 2023)
In this research describes the implementation of a water tower control system at Klabat University to control the filling of water in the reservoir. The implementation of this research was made to solve water problems that often occur at PDAM Tirtanadi These problems arise because the control is still done manually. This system can replace the role of officers in controlling the filling of reservoirs so that the water problems that often occur are avoided. The method used in this research is the Software Engineering (RPL) method and uses the Prototyping model process. The design of this system is implemented using several tools, namely a microcontroller, using a water level float sensor switch to detect the availability of water in the tub, and also using Sim900 to allow the system to send SMS notifications to officers. The final result of this research is the implementation of the Klabat University Water Tower Control System using a microcontroller.